2019
DOI: 10.1039/c9ta00819e
|View full text |Cite
|
Sign up to set email alerts
|

Constructing a highly oriented layered MOF nanoarray from a layered double hydroxide for efficient and long-lasting alkaline water oxidation electrocatalysis

Abstract: Template-directed synthesized Fe0.1-Ni-MOF nanoarray (Fe0.1-Ni-MOF/NF) behaves efficiently as an electrocatalyst for alkaline water oxidation with a strong electrochemical durability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
85
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 129 publications
(89 citation statements)
references
References 37 publications
4
85
0
Order By: Relevance
“…[15][16][17] Sacrificing MOFs as precursors and porous templates for desired target products preparation seems is an ideal solution and has been widely investigatedb efore, [15,18] which however is usually energy intensive and may do harm to both the living environmenta nd the periodic porous structures of MOFs. [16,19] Zheng'sg roup reported that vertically oriented CoNi-MOF from aC o(OH) 2 nanoarray acts as an efficient electrode materialw ith ah igh specific capacitance of 1044 Fg À1 at 2Ag À1 for asymmetrics upercapacitors. [17] Sacrificing targetm aterials with unique nanostructures might be another choice to tap the potentialo fM OFs for supercapacitors.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…[15][16][17] Sacrificing MOFs as precursors and porous templates for desired target products preparation seems is an ideal solution and has been widely investigatedb efore, [15,18] which however is usually energy intensive and may do harm to both the living environmenta nd the periodic porous structures of MOFs. [16,19] Zheng'sg roup reported that vertically oriented CoNi-MOF from aC o(OH) 2 nanoarray acts as an efficient electrode materialw ith ah igh specific capacitance of 1044 Fg À1 at 2Ag À1 for asymmetrics upercapacitors. [17] Sacrificing targetm aterials with unique nanostructures might be another choice to tap the potentialo fM OFs for supercapacitors.…”
Section: Introductionmentioning
confidence: 99%
“…[23] Additionally,t he band at 547 cm À1 may due to the stretching mode of MnÀOa nd NiÀOi nM n 0.1 -Ni-MOF, indicating the successful formation of metal-oxo between metal atoms and the -COO À groups of terephthalic acid linkers, which benefits the H 2 Oa vailability with hydrophilic property. [19,23] Since metallic NiÀNi bond for NF substrate is not Raman sensitive,t he vibrationm odes of the terephthalica cid ligand in Mn 0.1 -Ni-MOF dominate the Raman spectrumf or Mn 0.1 -Ni-MOF/NF (Figure 1c). [19,24] Three bands at 1614, 1561, and 1139 cm À1 correspond to the out-of-plane and in-plane stretching deformation modes of C=Ca nd C=CÀHb onds on the benzene ring, and the band at 1390 cm À1 can also be assigned to C=Cb ond stretching but with C=CÀCb ending.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Self‐supported metal‐organic frameworks (MOFs) with inexpensive transition metals or metal clusters and functionalized organic ligands in situ grown on the conductive substrates have emerging as promising OER electrocatalysts due to their adjustable compositions, well‐tailorable microstructures, and increased conductivity . Up to date, lots of layered monometallic Co‐, Ni‐, Fe‐, and bimetallic NiFe‐, FeCo‐, NiCo‐MOFs with aromatic dicarboxylate ligands (terephthalate, 2‐aminoterephthalate, 2,6‐naphthalenedicarboxylate, 2,5‐dihydroxybenzenedicarboxylate, 1,4‐naphthalenedicarboxylate and so on) have been directly anchored on the three‐dimensional conductive Ni foam (NF), porous γ‐Al 2 O 3 , NiFe alloy foam through ultrasonic method, chemical deposition, hydro/solvothermal approach, semisacrificial template growth, and dissolution‐crystallization mechanism , . It was found that various factors including the feed ratio of the reactant components, preparation process, condition control, and characterization method have been found to be significantly regulated the morphologies and electronic structures of the resulting electrocatalysts.…”
Section: Introductionmentioning
confidence: 99%